2018
DOI: 10.1097/mpg.0000000000001976
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cytomegalovirus in Colonic Mucosa of Children With Inflammatory Bowel Disease

Abstract: CMV presence is uncommon in colonic mucosa of children with IBD. Studies examining the underlying sero-prevalence of CMV and its role of reactivation of colitis are required to determine if the current recommendation for routine sigmoidoscopy to exclude CMV infection in corticosteroid-refractory acute severe colitis is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…In moderate to severe UC adult patients, CMV colitis is observed in 25–30% [ 43 , 44 , 45 ], especially those exhibiting steroid refractory disease [ 46 ]. The detection of CMV in colonic mucosa is less frequent in IBD children than in adults [ 47 ], probably because of lower seroprevalence of CMV infection in the pediatric population [ 48 ] and lower risk of viral reactivation; however, the consequences of CMV colitis on IBD evolution is similar to that observed in adults [ 49 , 50 ]. CMV colitis can reveal the inflammatory disease which was not diagnosed until the viral episode [ 51 ].…”
Section: Controversial Role Of CMV Infection In Ibd Inflammatory Fmentioning
confidence: 99%
“…In moderate to severe UC adult patients, CMV colitis is observed in 25–30% [ 43 , 44 , 45 ], especially those exhibiting steroid refractory disease [ 46 ]. The detection of CMV in colonic mucosa is less frequent in IBD children than in adults [ 47 ], probably because of lower seroprevalence of CMV infection in the pediatric population [ 48 ] and lower risk of viral reactivation; however, the consequences of CMV colitis on IBD evolution is similar to that observed in adults [ 49 , 50 ]. CMV colitis can reveal the inflammatory disease which was not diagnosed until the viral episode [ 51 ].…”
Section: Controversial Role Of CMV Infection In Ibd Inflammatory Fmentioning
confidence: 99%
“…Some authors recommend FFPE tissue CMV PCR as an additional method besides IHC to recognize further patients who will benefit from anti-CMV treatment (38) CMV-PCR on tissue biopsy is claimed in some studies to be a useful marker, especially in early phases of CMV infection with a sensitivity and reliability comparable to that of IHC (19,41,42), while some other studies indicate a poor correlation between results of tissue CMV PCR and CMV IHC. Highly sensitive PCR assays can provide false positive results leading to unnecessary treatment (35,43). In addition, in our follow-up information the majority of tissue CMV PCR-positive cases did not have poor clinical course, but cases with positive IHC, though much less frequent, showed higher adverse outcome rates despite treatment.…”
Section: Discussionmentioning
confidence: 61%
“…A systematic review of the adult IBD literature showed the highest rates of CMV colitis when using tissue PCR (9). However, a study of children with moderate-to-severe IBD showed that all "CMV colitis" patients with a qualitative tissue PCR diagnosis improved without antiviral therapy (21), possibly indicating the detection of clinically insignificant viral DNA by PCR. We examined routine histopathology for primary diagnosis of CMV colitis as it is the most accepted method in the literature (12,13,17).…”
Section: Discussionmentioning
confidence: 99%